Endothelial Dysfunction Using Flow-Mediated Dilatation Among Individuals with Pre-Impaired Glucose Tolerance (Pre-IGT) - Salmon, Jeannine Ann; Magbuhat, Ann Lorraine; Guerrero-Sali, Ruby Jane; Purino, Francis; Macindo, John Rey; Mercado-Asis, Leilani (Journal of the ASEAN Federation of Endocrine Societies, 2024)
Objectives. Pre-impaired glucose tolerance (pre-IGT) is a prediabetes stage characterized by normoglycemia and compensatory hyperinsulinemia due to insulin resistance. Hyperinsulinemia increases cardiovascular disease (CVD) risk, especially, endothelial dysfunction (ED). However, there is paucity of studies on ED with hyperinsulinemia alone, particularly in individuals with pre-IGT. This study aimed to determine the presence of ED using brachial artery flow-mediated dilatation (FMD) among adult participants with pre-IGT and its correlation with insulin levels and other related clinical parameters. Methodology. This is a cross-sectional analytical study. We screened adult patients with risk factors for developing diabetes (first-degree relative with type 2 diabetes mellitus, obesity, history of gestational diabetes and polycystic ovary syndrome). Brachial artery FMD was performed among participants with pre-IGT and findings were correlated with CVD risk factors using Pearson’s correlation and linear regression. Results. Of the 23 pre-IGT patients, 5 (21.74%) had decreased FMD values with significant associations with serum insulin and HbA1c. It was further observed that for every 1-unit increase in second-hour serum insulin and in HbA1c, there was a decrease in FMD values by 0.38% and 0.50%, respectively. Serum insulin was elevated, while other biochemical parameters were normal. Moreover, participants with low FMD were older, with higher BMI and had higher HBA1c, total cholesterol and low-density lipoprotein (LDL) cholesterol. Conclusion. As early as the pre-IGT stage, endothelial dysfunction using the FMD test is already present, with red flags on other CVD risk factors already developing. etes stage characterized by normoglycemia and compensatory hyperinsulinemia due to insulin resistance. Hyperinsulinemia increases cardiovascular disease (CVD) risk, especially, endothelial dysfunction (ED). However, there is paucity of studies on ED with hyperinsulinemia alone, particularly in individuals with pre-IGT. This study aimed to determine the presence of ED using brachial artery flow-mediated dilatation (FMD) among adult participants with pre-IGT and its correlation with insulin levels and other related clinical parameters. Methods: This is a cross-sectional analytical study. We screened adult patients with risk factors for developing diabetes (First-degree relative with type 2 diabetes mellitus, obesity, history of gestational diabetes, and polycystic ovary syndrome). Brachial artery FMD was performed among participants with pre-IGT, and findings were correlated with CVD risk factors using Pearson’s correlation and linear regression. Results: Of the 23 pre-IGT patients, five (21.74%) had decreased FMD values with significant associations with serum insulin and HbA1c, wherein every 1-unit increase in second-hour serum insulin and in HbA1c decrease FMD values by 0.38% and 0.50%, respectively. Serum insulin was elevated, while other biochemical parameters were normal. Moreover, participants with low FMD were older, more obese, and have higher HBA1c, total cholesterol, and LDL. Conclusion: As early as the pre-IGT stage, endothelial dysfunction using FMD test is already present, with red flags on other CVD risk factors already developing.